Australia : Staff Report for the 2004 Article IV Consultation. (IMF Staff Country Reports; Country Report ;, 2004)
Australia's 2004 Article IV Consultation reports that economic growth has rebounded, underpinned by continued buoyancy of domestic demand, an improvement in the external environment, and a gradual recovery from the drought. The main risk to the outlook relates to overheating in the housing market, but recent indicators suggest a soft landing is likely. Other risks include a re-emergence of drought, sustained high oil prices, or a weakening of external demand.